A Case Study on Ayurvedic Management of Kitibha Kushtha (Psoriasis) (International Journal of Ayurveda and Pharma Research, 2021)
In Ayurveda, Kushtha is a broad term including all types of skin diseases. Kitibha kushtha, one of the Kshudra kushtha (minor skin ailment) has most similarities with the symptoms of Psoriasis which is the most prevailing skin disease in today’s era. It affects almost 2% worldwide population. The high chances of recurrence and its reluctant nature makes it a matter of concern for modern medicine as they have a limited line of treatment. But in the case of Ayurveda, Shamana (pacifying treatment) and Shodhana chikitsa (detoxification treatment) along with Nidan parivarjan (abstinence from disease causing factors) play an important role in overcoming this disease. In this case study of Kitibha kushtha we have effectively managed the disease by the means of Virechan (purgation) and Shamana chikitsa.